Effects of Wireless Remote Microphone on Speech Recognition in Noise for Hearing Aid Users in China - Chen, Jing; Wang, Zhe; Dong, Ruijuan; Fu, Xinxing; Wang, Yuan; Wang, Shuo (Frontiers in Neuroscience, 2021)
Objective This study was aimed at evaluating improvements in speech-in-noise recognition ability as measured by signal-to-noise ratio (SNR) with the use of wireless remote microphone technology. These microphones transmit digital signals via radio frequency (RF) directly to hearing aids and may be a valuable assistive listening device (ALDs) for the hearing-impaired population of Mandarin speakers in China. Methods Twenty-three adults (aged 19 to 80 years old) and fourteen children (aged 8 to 17 years old) with bilateral sensorineural hearing loss were recruited. The Mandarin Hearing in Noise Test (MHINT) was used to test speech recognition ability in adult subjects, and the Mandarin Hearing in Noise Test for Children (MHINT-C) was used for children. The subjects’ perceived SNR was measured using sentence recognition ability at three different listening distances of 1.5 meters, 3 meters, and 6 meters. At each distance, SNR was obtained under three device settings: hearing aid microphone alone, wireless remote microphone alone, and hearing aid microphone and wireless remote microphone simultaneously. Results At each test distance, for both adult and pediatric groups, speech-in-noise recognition thresholds were significantly lower with the use of the wireless remote microphone in comparison with the hearing aid microphones alone (P<0.05), indicating better SNR performance with the wireless remote microphone. Moreover, when the wireless remote microphone was used, test distance had no effect on speech-in-noise recognition for either adults or children. Conclusions Wireless remote microphone technology can significantly improve speech recognition performance in challenging listening environments for Mandarin speaking hearing aid users in China.